PENGARUH MODEL PEMBELAJARAN KOOPERATIF SCRAMBLE TIPE TGT (TEAMS GAMES TOURNAMENT) TERHADAP PENINGKATAN JIWA KOMPETITIF SISWA PADA MATA PELAJARAN PAI - Ayu Nur Chamidah; Yogi Prana Izza; Ulva Badi’ Rohmawati (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Cooperative learning is an educational method that emphasizes student cooperation to achieve goals. This approach is believed to increase students' active participation as well as their academic and social abilities. Torneo Team Game (TGT) is one of the popular and successful cooperative learning models. This TGT model combines elements of games and tournaments to increase student interest and motivation in learning. The aim of implementing the TGT type scramble cooperative learning model is to improve student learning achievement, foster a spirit of cooperation, and build healthy competition in the classroom. Through this model, students are expected to be more active in the learning process, improve their ability to communicate and collaborate with peers, and have higher motivation to achieve better learning achievements. (1) planning, (2) implementation, and (3) evaluation are part of this research methodology. This research also involves forming small, heterogeneous teams based on students' academic abilities. At the implementation stage, students are divided into small teams and given learning material as a group. The research results show that cooperative learning using the TGT model can increase students' understanding of subject matter, improve social skills, and foster learning motivation through healthy competition. Students who are involved in learning with this model show significant improvements in terms of active participation and collaboration between friends. student achievement. Therefore, the TGT type cooperative learning model can be considered as a useful alternative to improve the quality of education and students' overall abilities.